Making friends - Ormerod, Jan. (New York : Lothrop, Lee & Shepard Books, 1987)
A baby plays with cloth, thread, buttons, and other materials while his pregnant mother is using them to make a doll for him.
1.8
K-3
K-3
Notable/Best Books (A.L.A.)
School Library Journal
Kirkus Review
Keywords: Babies -- Fiction; Dolls -- Fiction; Play -- Fiction; Dolls -- Fiction; Play -- Fiction; Infants -- Fiction